(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Lestari SR, Choliq FA, Sektiono AW, Hadi MS, Aditya HF, Rahmadhini N, Kusuma RM, Setiawam Y. 2022. Screening of quorum quenching activity of rhizobacteria against Pectobacterium carotovorum subsp. carotovorum. Biodiversitas 23: 4336-4342. Quorum sensing (QS) is a mechanism for determining the virulence of the phytopathogenic bacterium Pectobacterium carotovorum. P. carotovorum carries out the QS mechanism with the chemical compound acyl-homoserine lactone (AHL) to signal and carry out its pathogenicity and virulence. The pathogenicity of P. carotovorum can be prevented through quorum quencher (QQ) activity derived from bacteria that degrade AHL compounds by producing AHL-lactonase. In the present investigation, AHL-lactonase-producing bacteria were isolated from the rhizosphere of carrot cultivation in Bumiaji Sub-District, City of Batu, East Java, Indonesia. The isolated bacteria were screened for quorum quenching activity. Out of thirty-seven isolates, 7 rhizospheric bacteria showed QQ activity against the Chromobacterium violaceum bioindicator. The hypersensitivity test on tobacco plants showed that, five strains SRL07, SRL09, SRL15, SRL21, and SRL35 did not cause a hypersensitivity response. The five isolates were able to suppress the virulence of P. carotovorum in carrot tubers. The 16S rRNA gene sequences of the five isolates had the highest similarity to Bacillus thuringiensis, B. subtilis, and B. cereus. The five isolates were detected to have the gene encoding AHL-lactonase (aiiA). The present study provides new information about the QQ activity of rhizosphere and its potential as a quorum quencher against P. carotovorum.